Coreceptors and Their Ligands in Epithelial γδ T Cell Biology - Witherden, Deborah A.; Johnson, Margarete D.; Havran, Wendy L. (Frontiers in Immunology, 2018)
Epithelial tissues line the body providing the body with a protective barrier from the external environment. Maintenance of these epithelial barrier tissues critically relies on the presence of a functional resident T cell population. In some tissues, the resident T cell population is exclusively comprised of gamma delta T cells, while in others gamma delta T cells are found together with, alpha beta T cells and other lymphocyte populations. Epithelial resident gamma delta T cells function not only in the maintenance of the epithelium, but are also central to the repair process following damage from environmental and pathogenic insults. Key to their function is the crosstalk between gamma delta T cells and neighboring epithelial cells. This crosstalk relies on multiple receptor-ligand interactions through both the T cell receptor and accessory molecules leading to temporal and spatial regulation of cytokine, chemokine, growth factor and extracellular matrix protein production. As antigens that activate epithelial gamma delta T cells are largely unknown and many classical costimulatory molecules and coreceptors are not used by these cells, efforts have focused on identification of novel coreceptors and ligands that mediate pivotal interactions between gamma delta T cells and their neighbors. In this review, we discuss recent advances in the understanding of functions for these coreceptors and their ligands in epithelial maintenance and repair processes.